Angiogenesis: Growth Points. (May 2014) - Egginton, Stuart; Birot, Olivier
Abstract This collection of papers is based on talks presented at the IUPS meeting in Birmingham, UK last summer, in a symposium as part of the ESM & EVBO program, sponsored by the British Microcirculation Society and Microcirculation. In this issue we discuss new insights into the control of angiogenesis, including regulation of different aspects of endothelial cell biology by the tissue stroma, during inflammatory disease, and active remodelling of the microcirculation. We address a variety of signalling modes that determine the endothelial responses to pro‐angiogenic stimuli, including necessary synergy among different pathways and processes. We present an update of recent developments, and identify some areas where significant progress will likely occur.